China's Dilemma: Economic Growth, the Environment and Climate Change - Song, Ligang (ANU Press, 2008)
China's Dilemma-Economic Growth, the Environment and Climate Change examines the challenges China will have to confront in order to maintain rapid growth while coping with the global financial turbulence, some rising socially destabilising tensions such as income inequality, an over-exploited environment and the long-term pressures of global warming. China's Dilemma discusses key questions that will have an impact on China's growth path and offers some in-depth analyses as to how China could confront these challenges. The authors address the effect of the global credit crunch and financial shocks on China's economic growth; China's contribution to greenhouse gas emissions and emissions reduction schemes; the environmental consequences of foreign direct investment in China; the relationship between air pollution and mortality; the effect of climate change on agricultural output; the coal industry's compliance with tougher regulations; and the constraints water shortages may impose on China's economy. It also emphasises the importance of managing the rising demand for energy to moderate oil price increases and placating domestic and international concerns about global warming. In the thirty years since China started on the path of reform, it has emerged as one of the largest and most dynamic economies in the world. This carries with it the responsibility to balance the requirements of key industries that are driving its development with the need to ensure that its growth is both equitable and sustainable. China's Dilemma highlights key lessons learned from the past thirty years of reform in order to pave the way for balanced and sustained growth in the future.